Land Reform, Market Adjustment, and Rice Market Growth in Vietnam - Laiprakobsup, Thanapan; Chorkaew, Sunisa (Studies of Transition States and Societies, 2018)
Vietnam is in transition in terms of economic development. Its economic sectors have seen incredible growth for decades, including agriculture. Vietnam’s rice sector has increasingly expanded for decades regarding production and exports, while the country has experienced structural adjustment and policy reform, such as land reform. This article examines the production and trade effect of policy reform on the rice sector in Vietnam from 1976 to 2014. Using ordinary least squares model and marginal effects, the study found that policy reform has a positive effect on rice production and exports in Vietnam. Moreover, it was found that the Doi Moi macroeconomic reform has had a strong and positive effect on rice exports. This result shows that policy transition contributes to an increase in rice production and exports.